Studying the impact of chitosan salicylaldehyde/schiff base/CuFe2O4 in PC3 cells via theoretical studies and inhibition of PI3K/AKT/mTOR signalling - Ghada H. Elsayed; Asmaa M. Fahim (Scientific Reports)
Abstract In this elucidation, the nucleophilic attack of salicyladehyde with chitosan, which was obtained from the shrimp shell, afforded the cellulose aldehyde (Schiff base), and then the dispersion of CuFe2O4 on the surface of cellulose aldehyde gave the novel nanomaterial of bimetallic oxide, which was confirmed through spectral analysis such as FT-IR, NMR, SEM, and XRD analysis. Moreover, the anti-proliferative effect of chitosan, chitosan salicylaldehyde, and chitosan salicylaldehyde/CuFe2O4 was evaluated in PC3 human prostate cancer cells and HSF normal human skin fibroblasts. After 48 h, PC3 cell proliferation was significantly inhibited by chitosan salicylaldehyde/CuFe2O4 and chitosan salicylaldehyde (IC50 = 35.3 and 45.55 µg/ml, respectively) without any effects on normal HSF cells. The mRNA expression levels of PI3K, AKT, mTOR, and CCND1 were examined in PC3-treated cells by using QRT-PCR, and the results demonstrated that, by down-regulating the expression levels of these genes, chitosan salicylaldehyde/CuFe2O4 significantly affected prostate cancer cell proliferation, progression, and autophagy more than chitosan salicylaldehyde. Furthermore, the docking stimulation of the chitosan derivatives with different proteins showed the presence of CuFe2O4 particles effect on the interaction inside their pockets and increased the activities, and it’s related to biological evaluation. Additionally, the theoretical investigation of these chitosan derivatives and the determination of their physical descriptors showed the activity of bimetallic oxide and the presence of electrostatic hydrogen bond interaction. Finally, these findings may suggest that chitosan salicylaldehyde/CuFe2O4 has a promising anticancer impact against prostate cancer.